Analisis Fashal dan Washal sebagai Pemisah dan Penghubung Kalimat dalam Surat As-Sajadah Ayat 2 dan 4 - Azlan Nasution; Nafis Hasibuan (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This study examines the use of fashl and washl as linguistic devices that have an important role in forming the structure and meaning of sentences in Surah As-Sajadah verses 2 and 4. Through in-depth text analysis, this study attempts to reveal how the use of fashl and washl can influence the understanding of the messages conveyed in these verses. The results of the study show that fashl and washl not only function as mechanical tools to connect or separate sentences, but also have deep aesthetic and meaningful dimensions. This study is expected to contribute to the development of Qur'anic studies, especially in the field of balaghah science.